Ecotoxicidade de microplásticos de polietileno e nanopartículas de dióxido de titânio isolados e conjugados nas brânquias e fígados de girinos de Aquarana catesbeiana (Shaw, 1802) - Fujiwara, Gabriel Hiroshi (2025)
Currently, according to the Second Global Amphibian Assessment, habitat degradation is recognized as one of the main causes of amphibian population decline, with pollution being a major contributing factor to this loss. Among the emerging pollutants that have gained attention—both for their economic relevance and their potential environmental impacts—are microplastics and nanomaterials. Although the individual effects of these pollutants on amphibians have already been studied, significant gaps remain regarding the combined responses triggered by different classes of microplastics and nanoparticles. Given the urgency of understanding this ecotoxicological dynamic, the present study aimed to evaluate the responses of oxidative stress biomarkers, antioxidant enzymatic activity, and detoxification processes in the livers and gills of bullfrog (Aquarana catesbeiana) tadpoles exposed to polyethylene microplastics (PE-MPs) (60 mg/L) and titanium dioxide nanoparticles (TiO₂-NPs) (10 μg/L), both individually and in combination, after 15 days of exposure. Laboratory analyses demonstrated that co-exposure to microplastics and nanoparticles induced greater responses in both organs. In the gills, the mixture of these compounds resulted in increased activity of superoxide dismutase (SOD), while the groups treated individually with PE-MPs or TiO₂-NPs showed no significant changes in enzymatic levels or oxidative stress indicators. In the liver, co-exposure led to increased activity of glutathione S-transferase (GST) and elevated levels of lipid peroxidation. In the group exposed only to PE-MPs, an increase in SOD activity and lipid peroxidation levels were observed. On the other hand, neither organ exposed exclusively to TiO₂-NPs exhibited significant alterations in the analyzed parameters. These results reveal the complexity of interactions between these two contaminants and highlight the importance of studying the toxicological effects of pollutants across different organs, considering that each tissue may respond differently to various substances and that the distribution of these compounds within the organism is not uniform. Furthermore, additional studies are needed to understand the mechanisms underlying these biochemical responses, as well as further investigations into how these substances may impact other amphibian species and the ecosystems they inhabit.